Anodic Voltammetry of Epinephrine at Graphene-Modified Conductive Diamond Electrodes and Its Analytical Application. Issue 11 (1st January 2018) - Marcu, Maria; Spataru, Tanţa; Calderon-Moreno, Jose Maria; Osiceanu, Petre; Preda, Loredana; Spataru, Nicolae
Abstract : The electrochemical behavior of epinephrine at graphene-modified boron-doped diamond (GR/BDD) electrodes was studied in phosphate buffer solution within pH range from 4.6 to 10. Cyclic voltammograms, recorded for GR/BDD and boron-doped diamond (BDD) at pH 7, attest that, in the first case, the peak associated to the oxidation of epinephrine to adrenalinquinone is negatively shifted by around 350 mV and much sharper and higher. It appears that the presence of the graphene layer promotes the overall oxidation process. Additional investigations carried out at different pH, point out that the best sensitivity of GR/BDD toward epinephrine oxidation is obtained at pH 7. The calibration plot at pH 7 exhibited a certain decrease of the sensitivity from a rather high value 3.00 μA cm −2 μM −1 within the concentration range 1 μM–10 μM to a satisfactory one of 0.45 μA cm −2 μM −1 at higher epinephrine content, suggesting that GR/BDD electrode may be used for trace analysis. Epinephrine detection in the presence of uric acid, with relevance for the detection of biological compounds, can be achieved at relatively low or high pH, in which cases, two peaks situated at 0.229 V and 0.356 V, corresponding to epinephrine and uric acid oxidation, are evidenced.